1972
DOI: 10.1097/00006842-197211000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Pain Tolerance: Differences According to Age, Sex and Race

Abstract: The nature and extent of group differences in pain tolerance according to age, sex and race were examined. The method of pain tolerance determination was mechanical pressure on the Achilles tendon, performed on 4 1 , 119 subjects as part of the Kaiser-Permanente Automated Multiphasic Screening examination. The results showed that, on the average, a) pain tolerance decreases with age; b) men tolerate more pain than women; and c) Whites tolerate more pain than Orientals, while Blacks occupy an intermediate posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
151
3
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(169 citation statements)
references
References 21 publications
9
151
3
2
Order By: Relevance
“…There are well-documented race differences in experimental pain sensitivity, with Black individuals having a lower tolerance than White individuals for heat, cold, and ischemic pain 6,13,14,46 . Various psychosocial factors may account for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…There are well-documented race differences in experimental pain sensitivity, with Black individuals having a lower tolerance than White individuals for heat, cold, and ischemic pain 6,13,14,46 . Various psychosocial factors may account for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Pain tolerance has been found to be higher for males, whites, and younger age groups (Bobey & Davidson, 1970;Joy & Barger, 19 77;Merskey, 1973;Weisenberg, 1977;Weisenberg, Kreindler, Schachat, & Werboff, 1975;Woodrow, Friedman, Siegelaub, & Collen, 1972).…”
Section: Psychological Aspects Of Burn Patientsmentioning
confidence: 99%
“…Although pain threshold and tolerance have been found to be related, it has been observed that measures of pain tolerance had greater clinical utility (Frederiksen, Lynd, & Ross, 197 8;Merksey, 1973;Rybstein-Blinchik & Zaretsky, 1979;Weisenberg, 1977;Woodrow et al, 1972).…”
Section: Psychological Aspects Of Burn Patientsmentioning
confidence: 99%
See 2 more Smart Citations